2021
DOI: 10.1097/md.0000000000027719
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of oral pre-exposure prophylaxis (PrEP) uptake among individuals in a HIV vaccine preparedness cohort in Masaka, Uganda

Abstract: Oral pre-exposure prophylaxis (PrEP) significantly reduces human immunodeficiency virus (HIV) acquisition risk. However, data on predictors of PrEP uptake in sub-Saharan Africa are limited. We assessed predictors of PrEP uptake among HIV-uninfected high risk individuals enrolled in a HIV vaccine preparedness study in Masaka, Uganda.Between July 2018 and October 2020, we recruited adults (18–40 years) from sex work hotspots along the trans-African highway and Lake Victoria fishing communities. We collected base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Predictors of protective adherence in our study included being older (aged over 35 years), which was also identified in other Sub-Saharan studies [19,20,45]. This age-related trend may be explained by the hope to increase in life expectancy when engaging in a high-risk occupation like sex work as women as seen in another Ugandan study [46].…”
Section: Plos Onesupporting
confidence: 80%
“…Predictors of protective adherence in our study included being older (aged over 35 years), which was also identified in other Sub-Saharan studies [19,20,45]. This age-related trend may be explained by the hope to increase in life expectancy when engaging in a high-risk occupation like sex work as women as seen in another Ugandan study [46].…”
Section: Plos Onesupporting
confidence: 80%
“…Some of these earlier studies were mostly conducted in relatively homogenous populations from small fairly well-defined geographical areas with the study procedures conducted within participants’ communities [ 8 ] or at study clinics that were located not too far away (10–40 km) [ 5 , 7 ]. In contrast, our study was conducted in a more heterogeneous population spread over a wide geographical area (up to 80 km from the study clinic) [ 10 ]. The national COVID-19 control measures that were instituted from March 2020 onwards also contributed to the high LTFU observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We used data from an ongoing HIV vaccine-preparedness cohort study, “The PrEPVacc Registration Cohort Study”. The study was set up at sites in Tanzania, Mozambique, South Africa, and Uganda to prepare a population of HIV-negative individuals at risk of acquiring HIV for possible participation in the PrEPVacc HIV vaccine efficacy trial [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…At enrolment and quarterly visits, individuals received HCT and for those that tested HIV‐negative, counselling on and referrals for PrEP where it was available [ 16 , 18 ]. Oral Truvada (TDF/FTC) was available on site in Durban and through referral to a local provider in Masaka from 2018 when the PrEPVacc registration cohort was initiated.…”
Section: Methodsmentioning
confidence: 99%
“…The target population for the PrEPVacc registration cohort study comprised adults (18-45 years) at high-risk of HIV infection, that is, female sex workers (FSW), and female and male fisher folk in Masaka, Uganda; female bar workers and FSW in Dar es Salaam and Mbeya, Tanzania; men who have sex with men (MSM), FSW and other at risk individuals from the general population in Maputo, Mozambique; and the general population in areas of known high HIV incidence in Durban, South Africa [17].…”
Section: Study Design and Populationmentioning
confidence: 99%